C5-pyrimidine-functionalized morpholino oligonucleotides exhibit differential binding affinity, target specificity and lipophilicity. Issue 6 (12th January 2023) - Das, Arnab; Ghosh, Atanu; Sinha, Surajit
Abstract : 5-Substituted cytidine and uridine greatly enhance the duplex stability of PMOs with complementary DNA and RNA for better antisense applications. Abstract : C5-substituted uridine and cytidine morpholino chlorophosphoramidate monomers were synthesized and incorporated into a 12-mer Phosphorodiamidate Morpholino Oligonucleotide (PMO) using semi-automated solid phase synthesis. PMOs with most of the tested pyrimidine C5-substitutions have significantly increased thermal stability when bound to the complementary RNA strand relative to the PMO. They exhibit higher binding with RNA than DNA. CD-spectra show B-type helical conformation of duplexes. HPLC analysis indicates their greater lipophilicity compared to regular PMOs. These chemical modifications have significant potential towards the development of better antisense technologies.